Experimental Infection of the Genital Tract of Female Grivet Monkeys by Mycoplasma hominis: Effects of Different Routes of Infection - Møller, B. R. (1979)
In a previous study we produced acute salpingitis and parametritis in grivet monkeys by inoculation of Mycoplasma hominis directly into the uterine tubes. With the purpose of examining in the same animal model the effect of more natural routes of infection, six female grivet monkeys were inoculated, two by two, with M. hominis by the following methods: (experiment A) into the uterine cavity through the cervical canal; (experiment B) into the uterine cavity by the same route, but after ligature of the isthmus of the uterine tubes had been performed and followed by curettage of the endometrium; and (experiment C) into the cervical epithelium. Whereas the animals in experiment A developed no or only very slight signs of infection, all monkeys in experiments B and C developed pronounced gross and microscopic inflammatory lesions of the uterine tubes and parametria, together with a significant antibody response. It is concluded that ascending M. hominis infection of the genital tract must be preceded by mechanical injury of the epithelial barrier, and that subsequent spread of the infection occurs via blood and lymph vessels rather than by the canalicular route. The inflammatory genital tract disease produced experimentally with M. hominis in grivet monkeys is very similar in its pathogenesis and pathology to the type of salpingitis caused in humans by microorganisms other than Neisseria gonorrhoeae and Chlamydia trachomatis.